Thermo-ecological performance analysis of a double-reheat Rankine cycle steam turbine system (RCSTS) with open and close feed water heaters - Gonca, Guven (INDERSCIENCE ENTERPRISES LTD, 2018)
This study presents the exergetic and thermo-ecological performance optimisation of a Rankine cycle steam turbine system (RCSTS) consisting of three turbines, one open feed water heater (OFWH) and two closed feed water heaters (CFWHs). In this study, different performance characteristics such as effective power, effective power density, exergy efficiency, exergy destruction and ecological coefficient of performance (ECOP) are used to investigate and optimise the system performance. The effects of condenser pressure, OFWH pressure and reheat pressures on the performance characteristics of the system have been examined by considering the irreversibilities and system properties. The results showed that the component pressures considerably affect the system performance. Therefore, they should be optimised to obtain maximum performance characteristics.
Keywords: steam turbine; Rankine cycle; thermo-ecological optimisation; power density; ECOP; exergy; POWER-PLANT; EXERGY ANALYSES; RECOVERY; ENERGY; OPTIMIZATION; PARAMETERS; EFFICIENCY; DESIGN; SINGLE; AIR; Thermodynamics; Energy & Fuels